161k views
16 votes
HELPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPP

HELPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPPP-example-1

1 Answer

8 votes

Answer:

1) x=−y-2

2)x=−y+2

Explanation:

Let's solve for x.

y=−x−2

Step 1: Flip the equation.

−x−2=y

Step 2: Add 2 to both sides.

−x−2+2=y+2

−x=y+2

Step 3: Divide both sides by -1.

x=−y−2

Let's solve for x.

3x+3y=6

Step 1: Add -3y to both sides.

3x+3y+−3y=6+−3y

3x=−3y+6

Step 2: Divide both sides by 3.

x=−y+2

User FalseVinylShrub
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.